2023
DOI: 10.1136/bmjoq-2022-001965
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics promoting behaviour change: physician experience with a coalition-led quality improvement initiative to reduce excessive laboratory test ordering

Abstract: BackgroundAttempts have been made to reduce excessive laboratory test ordering; however, the problem persists and barriers to physician involvement in quality improvement (QI) remain. We sought to understand physician participation experience following a laboratory test overuse initiative supported by a QI coalition.MethodsAs part of a larger mixed-methods study, structured virtual interviews were conducted with 12 physicians. The Theoretical Domains Framework (TDF) and the Behavioural Change Wheel (BCW) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Mather et al considered these the most important domains along with ‘skills’, ‘roles and responsibilities’ and ‘confidence in own ability’ [ 57 ]. This is supported by other reviews that have identified the most important domains for practice change being ‘environmental context and resources’, ‘social influence’, ‘knowledge’, ‘beliefs about ability’, and ‘beliefs about consequences’ [ 44 , 58 ]. While there is a great deal of convergence of finding from all studies there are some notable exceptions.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Mather et al considered these the most important domains along with ‘skills’, ‘roles and responsibilities’ and ‘confidence in own ability’ [ 57 ]. This is supported by other reviews that have identified the most important domains for practice change being ‘environmental context and resources’, ‘social influence’, ‘knowledge’, ‘beliefs about ability’, and ‘beliefs about consequences’ [ 44 , 58 ]. While there is a great deal of convergence of finding from all studies there are some notable exceptions.…”
Section: Discussionsupporting
confidence: 62%
“…The importance of ‘social influence’ and ‘beliefs about capabilities’ across all studies emphasises the need to create opportunities for practitioner social support, coaching and building relationships. As Mathura found “relationships do matter, if you know somebody, and you trust them, it’s much more likely to do something that they are suggesting” [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future intervention strategies were identified from the alignment to the BCW intervention functions41 (figure 2): ‘(1) communication from a local, credible physician to facilitate participation ; (2) provide past examples of physician-led projects targeting laboratory test reduction ; (3) provide laboratory test utilisation reports with cost data to demonstrate negative consequence ; (4) apply guidelines (laboratory test ordering protocols) ; (5) limit test order frequency when results are normal ; (6) update laboratory order forms/electronic order panels to reduce unnecessary test ordering ; (7) provide support personnel (eg, QI and data personnel ); (8) offer QI and clinical laboratory medicine educational sessions ; (9) provide hands-on QI opportunity to apply knowledge and leadership ; (10) physician role-modelling QI to aspire to or imitate ; and (11) offer incentives such as remuneration and formalise physician QI roles to encourage involvement ’. 43 pg. 5…”
Section: Resultsmentioning
confidence: 99%
“…Detailed reporting of the qualitative phase is published elsewhere. 43 From the interviews, 809 statements were coded into 13 TDF domains that resulted in 9 overarching themes: '(1) QI education and hands-on opportunities support involvement; (2) physician mentorship; (3) coalition functions as a safe peer-to-peer QI community; (4) trusted local physician leader sharing QI encourages participation; (5) provide initiative approach, data and physician role; (6) order BUN tests mindfully, not reflexively or habitually; (7) changing physician behaviour is difficult; (8) opportunity to lead, with support, a straightforward QI intervention that requires minimal effort; and (9) physician-led QI competed out'. 43 pg.…”
Section: Qualitative Resultsmentioning
confidence: 99%